2021
DOI: 10.1055/s-0041-1735128
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Associated Factors in Postmenopausal Women

Abstract: Objective To assess the sexual function and associated factors in postmenopausal women. Methods This a descriptive, cross-sectional study with 380 women aged 40 to 65 years, users of public health services in 2019. Questionnaires were applied on demographic characteristics, on climacteric symptoms (menopause rating scale) and on sexual function (sexual quotient, female version). Bivariate and multiple analyses by logistic regression were performed, with adjusted odds ratios (ORad) and 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 35 publications
0
3
1
Order By: Relevance
“…Similarly to our results, Dąbrowska-Galas et al [23] reported that dyspareunia and lubrication were some of the most affected domains. On the other hand, sexual desire and orgasm were the ones that presented the least impact during the climacteric, contrary to what was reported by Trento et al [24].…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Similarly to our results, Dąbrowska-Galas et al [23] reported that dyspareunia and lubrication were some of the most affected domains. On the other hand, sexual desire and orgasm were the ones that presented the least impact during the climacteric, contrary to what was reported by Trento et al [24].…”
Section: Discussioncontrasting
confidence: 76%
“…On the other hand, sexual desire and orgasm were the ones that presented the least impact during the climacteric, contrary to what was reported by Trento et al . [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Greater palpitations were not related to sexual activity 61 , 76 or sexual function. 109 In another article, greater palpitations were significantly related to sexual dysfunction (total scores and subscales of infrequency, non-communication, dissatisfaction, avoidance, non-sensuality, vaginismus, and anorgasmia) in surgically menopausal women but not naturally menopausal women. 108 …”
Section: Resultsmentioning
confidence: 96%
“…Sexual relations are among the most important aspects of marital relations that are affected during menopause [ 3 ]. One of the problems faced by women during this period is pelvic floor muscle relaxation, vaginal dryness, urinary problems, painful intercourse, sexual dysfunction, and, consequently, sexual dissatisfaction [ 15 ]. These changes, however, can be adjusted and controlled using interventions such as education and technology-based interventions, leading to an improvement in sexual performance [ 5 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%